Analisis Kinerja Sistem Informasi pada PT. Bank Central Asia Menggunakan IT Balanced Scorecard - Achmad Fikri Syarif Mail; Prihanto Ngesti Basuki; Agustinus Fritz Wijaya (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
PT. Bank Central Asia (BCA) is the biggest private bank in Indonesia. It always offers various banking solutions which address customers’ financial needs. Through various high quality and targeted products and services, BCA financial solution supports personal financial planning and customers’ business development. KlikBCA Individual (KBI) is one of the services that BCA offers to enable customers have practical, safe, and easy banking transaction. Therefore, a thorough measurement of Information System (IS)/Information Technology (IT) application performance from several aspects toward this innovation is needed. It measures how good the service is for both company and customers. The methodology used in this research is IT Balanced Scorecard. The result shows that the highest perspective is the company contribution as much as 19.33%, followed by the future perspective as much as 19%, the user orientation perspective as much as 18.8%, and the last is operationalization perspective as much as 14.58%. The final result is 71.71%, which indicates that it has reached a good level.